Effect of rfaH (sfrB) and temperature on expression of rfa genes of Escherichia coli K-12. - Pradel, E (1991)
In order to study the regulation of a large block of contiguous genes at the rfa locus of Escherichia coli K-12 which are involved in synthesis and modification of the lipopolysaccharide core, the transposon TnlacZ was used to generate in-frame lacZ fusions to the coding regions of five genes (rfaQ, -G, -P, -B and -J) within this block. The beta-galactosidase activity of strains in which these fusions had been crossed into the chromosomal rfa locus was significantly decreased when the rfaH11 (sfrB11) allele was introduced and was restored to wild-type levels when these strains were lysogenized with a lambda phage carrying wild-type rfaH. This indicates that the positive regulatory function encoded by rfaH is required throughout this block of genes. In addition, expression of the lacZ fusion to rfaJ was reduced by growth at 42 degrees C, and this correlated with a temperature-induced change in the electrophoretic profile of the core lipopolysaccharide.